Knowledge Conversion Process in Managing Content Based on SECI Model and the Relationship Towards Product Development - Tasmin, Rosmaini; Ying Sherng, Toh (Research in Management of Technology and Business, 2020)
Firms today have more effectively started to engage towards the process of managing knowledge inside the organization. Top management realizes that the importance of utilizing the available knowledge in gaining competitive advantages. The implementation of knowledge management in a firm has played a part on managing all the knowledge across the organization to generate new ideas and to apply it onto the development of product and services. The process of knowledge conversion by converting tacit knowledge into explicit knowledge vice versa can help organization to create new knowledge. The application of Socialization-Externalization-Combination-Internalization (SECI) model, introduced by Nonaka and Takeuchi, differentiates the whole process of knowledge conversion of an organization into four modes of knowledge management cycle, which are socialization, externalization, combination and internalization. The relationship between knowledge conversion in product development is then compared to see whether the new knowledge can give influence towards development process in terms of customer and supplier, product development strategy and innovation of new product. It is found that the correlation between knowledge conversion and product development process is positive and significant among these manufacturing firms.